In God's shadow : politics in the Hebrew Bible - Walzer, Michael (Yale University Press, 2012)
Examines the laws, histories, prophecies and wisdom of the ancient biblical writers and discusses their views on justice, hierarchy, war, the authority of kings and priests and the experience of exile.